Gods, music and rainmaking in Yorùbáland - Atinúkẹ́ Adénìkẹ́ Láyadé; ‘Adebáyọ Oludare Ògúnyẹmí (Tydskrif vir letterkunde, 2025)
The salutation to Ṣàngó (Yorùbá god of thunder and lightning) exemplifies the deity through the depiction of his distinguishing volatile personality. His response to ensemble music reflects the possibilities of his influence as a facilitator of musical skills at Ṣàngó festivals and plays in Yorùbáland. The intricacies of African rhythms impact Ṣàngó’s emotions through praise singing with a Bàtá ensemble in a distinctive and impulsive way. However, the process that brings about rainfall appears not to have been sufficiently documented. In this study, we investigate the artistic form that causes rainfall whenever the salutation is rendered. Data was gathered through interviews and analysis of the play Ọba kò so by Dúró Ladipọ.  The study findings prove the connection between Ṣàngó, and rain through the lens of literature and traditional Yorùbá music and festivals in honour of Ṣàngó. By exploring this intersection of art, music and environmental phenomena, the study offers valuable insight into the complex relationships between humans, culture, and the natural force.